A Rusty Record of Weathering and Groundwater Movement in the Hyperarid Central Andes. (3rd August 2021) - Shaw, J. M.; Evenstar, L.; Cooper, F. J.; Adams, B. A.; Boyce, A. J.; Hofmann, F.; Farley, K. A.
Abstract: The Atacama Desert, on the western margin of the Central Andes, hosts some of the world's largest porphyry copper deposits (PCDs). Despite a hyperarid climate, many of these PCDs have undergone secondary "supergene" enrichment, whereby copper has been concentrated via groundwater‐driven leaching and reprecipitation, yielding supergene profiles containing valuable records of weathering and landscape evolution. We combine hematite (U‐Th‐Sm)/He geochronology and oxygen isotope analysis to compare the weathering histories of two Andean PCDs and test the relative importance of climate and tectonics in controlling both enrichment and water table movement. At Cerro Colorado, in the Precordillera, hematite precipitation records prolonged weathering from ∼31 to ∼2 Ma, tracking water table descent following aridity‐induced canyon incision from the late Miocene onward. By contrast, hematite at Spence, within the Central Depression, is mostly younger than ∼10.5 Ma, suggesting exhumation ended much later. A heavy oxygen isotopic signature for Spence hematite suggests that upwelling formation water has been an important source of groundwater, accounting for a high modern water table despite persistent hyperaridity, whereas isotopically light hematite at Cerro Colorado formed in the presence of meteoric water. Compared with published paleo‐environmental and sedimentological records, our data show that weathering can persist beneath appreciable post‐exhumation cover, under hyperarid conditions unconducive to enrichment. The susceptibility of each deposit to aridity‐induced water table descent, canyon incision and deep weathering has been controlled by recharge characteristics and morphotectonic setting. Erosional exhumation, rather than aridity‐induced water table decay, appears to be more important for the development of supergene enrichment. Plain Language Summary: Northern Chile hosts many large copper deposits which were formed at depths of several kilometers and then brought close to the surface during Andean mountain‐building. Water‐driven weathering reactions have upgraded some exhumed deposits by leaching copper from sulfide minerals under oxidizing conditions and reprecipitating it within new minerals under reducing conditions, in a process called supergene ("from above") enrichment. Relative water table descent is required for these processes to expand into fresh ore, but it is unclear whether climatic or tectonic factors have been more important controls on water table movement in different locations. In this study, we investigate the age and oxygen isotopic composition of the iron oxide weathering mineral, hematite, from the supergene profiles of two Andean copper deposits (Spence and Cerro Colorado) to constrain and compare the timing of weathering and sources of weathering fluids. The preserved record of weathering begins at ∼31 Ma at Cerro Colorado but the main period of weathering at Spence occurred after ∼10.5 Ma. Oxygen isotopes show that differing responses of the water table to increased aridity after the late Miocene (descending at Cerro Colorado but remaining shallow at Spence) have depended on catchments, groundwater flow, and differences in topography. Key Points: Hematite (U‐Th‐Sm)/He weathering geochronology constrains late Miocene exhumation rates in the Atacama Desert of northern Chile Hematite records prolonged post‐hyperaridity development of weathering profiles in the Atacama Desert Exhumation is the most important driver of relative water table descent during supergene enrichment of porphyry copper deposits